2001
DOI: 10.1002/eat.1051
|View full text |Cite
|
Sign up to set email alerts
|

Body image and personality predictors of eating disorder symptoms during the college years

Abstract: Findings are discussed in the context of the value of longitudinal designs in identifying risk factors. Dissatisfaction with one's figure seems to be consistently related to worsening eating pathology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
115
0
5

Year Published

2004
2004
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 186 publications
(125 citation statements)
references
References 26 publications
5
115
0
5
Order By: Relevance
“…Individuals might also use radical compensatory behaviors, such as vomiting, to reduce anxiety about impending weight gain consequent to overeating or because they believe that purging serves as an emotional catharsis. In support of this assertion, negative affect and temperamental emotionality have been found to predict future onset of bulimic pathology (Killen et al, 1996;Stice & Agras, 1998) and increases in bulimic symptoms (Cooley & Toray, 2001;Stice, 2001). Depressive symptoms have also been found to predict onset of binge eating (Stice, Presnell, & Spangler, 2002) and general eating pathology (Johnson, Cohen, Kotler, Kasen, & Brook, 2002).…”
Section: Bulimia Nervosa and Depressionmentioning
confidence: 80%
“…Individuals might also use radical compensatory behaviors, such as vomiting, to reduce anxiety about impending weight gain consequent to overeating or because they believe that purging serves as an emotional catharsis. In support of this assertion, negative affect and temperamental emotionality have been found to predict future onset of bulimic pathology (Killen et al, 1996;Stice & Agras, 1998) and increases in bulimic symptoms (Cooley & Toray, 2001;Stice, 2001). Depressive symptoms have also been found to predict onset of binge eating (Stice, Presnell, & Spangler, 2002) and general eating pathology (Johnson, Cohen, Kotler, Kasen, & Brook, 2002).…”
Section: Bulimia Nervosa and Depressionmentioning
confidence: 80%
“…1,2 This theory also suggests that individuals might use radical compensatory behaviors, such as vomiting or laxative abuse, to reduce anxiety about impending weight gain consequent to overeating or because they believe that purging provides an emotional catharsis. In support of this theory, depressive symptoms and negative affect have been found to predict future increases in bulimic symptoms, 3,4 as well as onset of binge eating, 5 bulimic pathology, [6][7][8] and general eating pathology. 9 Although several prospective studies have reported null findings for these relations (e.g., 1, 10-11), these studies were more likely to have used smaller samples and focused on general eating pathology outcomes.…”
Section: Introductionmentioning
confidence: 81%
“…Researchers found increase disordered eating behaviors and depression among adolescents who had bulimic problems 14 .There is inconsistent findings concerning the relationship between obesity and depression. Some studies included that there was no relation between obesity and depression 15 , while others reported that obese people had higher risk of depression 16 . Goodman and Whitaker showed that depressed adolescents are at increased risk to the development and persistence of obesity later in their life.…”
Section: Discussionmentioning
confidence: 99%